2018
DOI: 10.1111/hsc.12561
|View full text |Cite
|
Sign up to set email alerts
|

Australian general practitioner attitudes to residential aged care facility visiting

Abstract: Demographic trends suggest that the sustainability of the general practitioner (GP) Residential Aged Care Facility (RACF) workforce, worldwide and in Australia, is under threat, compromising the ongoing care of chronically ill RACF residents. It is therefore important to ascertain current GP attitudes towards this work, to better understand and hypothesise means of reversing this trend. To this end, during 2014 the views of 26 GPs and GP Registrars working in rural and regional New South Wales, Australia, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Identifying residents' goals, preferences, needs and values is an important aspect of person‐centred care in RACFs and a key strategy to achieve deprescribing to improve health outcome from medications . Importantly, this study shows that most RACFs do not actively identify and record resident goals and preferences for medications due to a range of factors, which places the responsibility on GPs who are already time poor . Most staff devolved the responsibility to the GP, due to beliefs that it was the duty of the GP and perceptions about professional boundaries.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Identifying residents' goals, preferences, needs and values is an important aspect of person‐centred care in RACFs and a key strategy to achieve deprescribing to improve health outcome from medications . Importantly, this study shows that most RACFs do not actively identify and record resident goals and preferences for medications due to a range of factors, which places the responsibility on GPs who are already time poor . Most staff devolved the responsibility to the GP, due to beliefs that it was the duty of the GP and perceptions about professional boundaries.…”
Section: Discussionmentioning
confidence: 91%
“…17 Importantly, this study shows that most RACFs do not actively identify and record resident goals and preferences for medications due to a range of factors, which places the responsibility on GPs who are already time poor. 18 Most staff devolved the responsibility to the GP, due to beliefs that it was the duty of the GP and perceptions about professional boundaries. Health-care professionals distancing themselves from responsibility and passing it onto others is consistent with previously identified barriers to the optimisation of medications in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…16 A recent qualitative study of Australian GP's perceptions identified poor remuneration, logistic issues, system inefficiencies and inadequate training as potential obstacles to treating older people in ACF. 17 Review of the relatively sparse literature published on Australian medical student attitudes toward older people found these to be measurably neutral to positive. Findings from qualitative research into student attitudes also captured by the review were mixed, with negative themes of nihilism, paternalism, communication challenge, perceptions of high morbidity and reduced quality of life.…”
Section: Open Accessmentioning
confidence: 99%
“…16 A recent qualitative study of Australian GP’s perceptions identified poor remuneration, logistic issues, system inefficiencies and inadequate training as potential obstacles to treating older people in ACF. 17 …”
Section: Introductionmentioning
confidence: 99%
“…This resource-poor environment may also have to deal with the unrealistic expectations of family members or residents for curative care when a more palliative approach is warranted, as in the care of people with end-stage dementia. The skills to deliver a more appropriate palliative approach may also be lacking (37)(38)(39)(40).…”
Section: Environment Surrounding the Evaluationmentioning
confidence: 99%